Proceedings of the 18th SIGSPATIAL International Conference on Advances in Geographic Information Systems 2010
DOI: 10.1145/1869790.1869817
|View full text |Cite
|
Sign up to set email alerts
|

Natural neighbor interpolation based grid DEM construction using a GPU

Abstract: With modern LiDAR technology the amount of topographic data, in the form of massive point clouds, has increased dramatically. One of the most fundamental GIS tasks is to construct a grid digital elevation model (DEM) from these 3D point clouds. In this paper we present a simple yet very fast algorithm for constructing a grid DEM from massive point clouds using natural neighbor interpolation (NNI). We use a graphics processing unit (GPU) to significantly speed up the computation. To handle the large data sets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…According to preliminary results, GPU algorithm decreased processing time by 900%. Beutel et al in [5] considered construction of a grid digital elevation model (DEM) from 3D point clouds generated by the LiDAR equipment. The obtained results showed that using of a graphics processing unit (GPU) for this type of GIS application can significantly speed up the computation.…”
Section: Cuda In Gismentioning
confidence: 99%
“…According to preliminary results, GPU algorithm decreased processing time by 900%. Beutel et al in [5] considered construction of a grid digital elevation model (DEM) from 3D point clouds generated by the LiDAR equipment. The obtained results showed that using of a graphics processing unit (GPU) for this type of GIS application can significantly speed up the computation.…”
Section: Cuda In Gismentioning
confidence: 99%
“…A handful of works has been done related to spatial data interpolation and DEM construction. Beutel et al (2010) realized a GPU-based natural neighbour interpolation algorithm to generate DEM and accomplished a 10 times speedup ratio. Xia et al (2011) implemented IDW algorithm on a GPU and made a range of speedups from 12 to 33 depending on the scale and resolution of dataset.…”
Section: Introductionmentioning
confidence: 99%
“…This massive set of points is called "point cloud." Modern airborne LiDAR technology can map the Earth's surface at a 15-20-cm horizontal resolution, and future generations of LiDAR scanners are expected to generate even higher resolution maps [1]. The large volume of scanned data that are manipulated when processing a LiDAR point cloud has been one of the major challenges in data processing.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [18] use a PC cluster and a virtual grid to create a raster DSM and then produce a digital terrain model using enormous amounts of airborne laser scanning data. Beutel et al [1] construct a grid DEM from massive point clouds using natural neighbor interpolation and get a 10× increase in speed using a graphics processing unit (GPU). Fieldprogrammable gate array (FPGA) [19] and cloud computing [20] are also used to improve processing efficiency.…”
Section: Introductionmentioning
confidence: 99%